Adropin: a key player in immune cell homeostasis and regulation of inflammation in several diseases - Wang, Junmin; Ding, Ning; Chen, Chong; Gu, Simin; Liu, Jing; Wang, Yanping; Lin, Liubing; Zheng, Yiyuan; Li, Yong (Frontiers in Immunology, 2025)
Adropin is a secreted peptide encoded by the energy homeostasis-associated gene (ENHO), located chromosome 9p13.3, with a conserved amino acid sequence across humans and mice. Its expression is regulated by various factors, including fat, LXRα, ERα, ROR, and STAT3. Adropin plays a critical role in glucose and lipid metabolism, as well as insulin resistance, by modulating multiple signaling pathways that contribute to the reduction of obesity and the improvement of blood lipid and glucose homeostasis. Additionally, it influences immune cells and inflammation, exerting anti-inflammatory effects across various diseases. While extensive research has summarized the regulation of cellular energy metabolism by adropin, limited studies have explored its role in immune regulation and inflammation. To enhance the understanding of adropin’s immune-modulating and anti-inflammatory mechanisms, this review synthesizes recent findings on its effects in conditions such as atherosclerosis, diabetes, fatty liver, non-alcoholic hepatitis, and inflammation. Furthermore, the review discusses the current research limitations and outlines potential future directions for adropin-related investigations. It is hoped that ongoing research into adropin will contribute significantly to the advancement of medical treatments for various diseases.